'Better housing conditions are of vital importance to the ordinary man': slum clearance in post-war Khartoum. (24th August 2015) - CURLESS, GARETH
ABSTRACT: As the population of Khartoum increased during the 1940s, the Sudan government sought to demolish the Deims that surrounded the southern edge of the city and relocate the residents to a new planned site. Here, it was envisaged that improved housing would help to create 'modern', model families. However, like many of the post-war housing projects in British Africa, the resettlement of the Deims was undermined by poor planning, inadequate financial support and resistance from residents, who rejected the colonial planners' vision of how domestic life should be organized.